Movement patterns and home range of wild and re‐stocked Arapaima gigas (Schinz, 1822) monitored by radio‐telemetry in Lake Imiria, Peru - Núñez Rodríguez, Jesús (2016)
The objectives of this study were the evaluation of the adaptation capabilities of re‐stocked Arapaima gigas and their individual behavioural movements (males and females) to the wild environment compared to wild individuals still present in Lake Imiria, Peru and their survival rates. Using radio telemetry (external transmitters, 75 × 17 mm diameter, 35 g in air, ATS, Isanti, MN, USA), adaptation and behaviour of externally tagged, restocked cage‐raised (124–143 cm TL, n = 14) and wild A. gigas (117–153 cm TL, n = 8), were monitored, focusing observations on individual behaviour and preferential localization in the lake. Home range size determined by minimum convex polygons (MCP95) or Kernel Density Estimation (KDE95) varied from 0.001 to around 4 km2, but the average KDE50 was relatively small (0.1 km2) in comparison to the tracked fish size (117–153 cm TL), indicating strong residency and presumably territoriality in this species. Also observed was that the habitat was concentrated along the shoreline of the lake and closely related to the presence of aquatic vegetation. Home range localization estimates and apparent travelled distance of wild and restocked fishes were very similar, thereby suggesting a rapid and good acclimation and survival of cultured re‐stocked fish to a natural environment.